PENGARUH SUMBER DAYA MANUSIA (SDM) TERHADAP KUALITAS SEDIAAN BASIL TAHAN ASAM (BTA) DI FASILITAS KESEHATAN KABUPATEN CILACAP PADA TAHUN 2022 - Anggih Priyanto; Ira Pangesti; Akhmad Mubarok (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2023)
Tuberculosis (TB) is a dangerous infectious disease that causes many deaths, and control needs to be carried out so that TB transmission and mortality rates can decrease. The COVID-19 pandemic has had an impact on TB elimination targets, so that targets have slowed, stopped or retreated. One of the efforts made to improve again is to carry out External Quality Control (PME) by the UPTD health laboratory of the Health Office to supervise that the quality of laboratory examinations in health facilities produces accurate and thorough examinations, therefore the Human Resources (HR) factor needs to be considered to obtain quality examination results. This study aims to determine the effect of human resources on the quality of BTA preparations in health facilities in Cilacap Regency in 2022. This study was conducted by analyzing the value of PME results on the quality of BTA preparations in 2022 with the results of questionnaire observation scores regarding human resources for 30 respondents in health facilities in Cilacap Regency who were randomly selected. Pearson correlation statistical test was used, resulting in a significant relationship between human resources and the quality of BTA preparations in health facilities in Cilacap Regency in 2022 with a value of 0.008 <0.05. The quality of specimens, size and thickness of the preparation have many discrepancies in the manufacture of BTA preparations in health facilities, training needs to be carried out routinely to control the quality of BTA preparations.